Literasi keuangan investor saham Indonesia - Faisal, Ridhan Adli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Financial literacy is highlighted as a key input in financial decisions that enable investors to increase the productivity of their financial capital. This study aims to determine the condition of the financial literacy of stock market investors in Indonesia. This research uses quantitative methods. The data collected is primary data collected through a questionnaire. The sampling method used is purposive sampling, where the respondent who can fill out the questionnaire is someone who invests in the Indonesia Stock Exchange (IDX). The results of this study state that investors have good financial literacy skills. However, if you look at financial literacy based on questions, there are big differences between understandings of financial literacy. The lowest level of financial literacy is in questions about products, compound interest, and the implications of purchasing stock. Thus, Indonesian investors need to further increase their understanding of this area. Regulators and private financial institutions can increase investors' financial literacy by conducting education in this field. The financial literacy of Indonesian stock investors significantly and positively influences the percentage of assets in shares. The higher the knowledge possessed by an investor, the more assets are allocated in shares.